2002
DOI: 10.1111/1467-9620.00179
|View full text |Cite
|
Sign up to set email alerts
|

When State Policies Meet Local District Contexts: Standards-Based Professional Development as a Means to Individual Agency and Collective Ownership

Abstract: This article focuses on how a statewide reform initiative, when envisioned as a professional development opportunity, impacted teachers’ capacities to become change agents in their classrooms and districts and how individual district contexts shaped the development of those capacities. The interview and artifact data used for this study were gathered from teachers and administrators in four demonstration districts that were involved in a standards-based professional development initiative within the federally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 11 publications
1
27
1
1
Order By: Relevance
“…Assumption Five: Teachers will have access to appropriate professional learning opportunities (Dutro, Fisk, Koch, Roop, & Wixson, 2002;Thompson & Zeuli, 1999). What is more, those teachers who are not fully prepared to teach to the ambitious learning standards, if not others, will take advantage of these learning opportunities, thereby developing the requisite knowledge, skills, and commitment, and their teaching practice will improve accordingly.…”
Section: Examining Assumptions About Teachers' Responses To State Stamentioning
confidence: 99%
See 1 more Smart Citation
“…Assumption Five: Teachers will have access to appropriate professional learning opportunities (Dutro, Fisk, Koch, Roop, & Wixson, 2002;Thompson & Zeuli, 1999). What is more, those teachers who are not fully prepared to teach to the ambitious learning standards, if not others, will take advantage of these learning opportunities, thereby developing the requisite knowledge, skills, and commitment, and their teaching practice will improve accordingly.…”
Section: Examining Assumptions About Teachers' Responses To State Stamentioning
confidence: 99%
“…Two lines of inquiry are especially helpful in investigating the first three assumptions underlying the reform theory of action (regarding teachers' attention to the reform; the seriousness with which they and others take the reform; and their adjustment of instruction to align with standards and associated assessments). The first line of inquiry concentrates on teachers' responses to aligned curricular reforms (e. g., Dutro, Fisk, Koch, Roop, & Wixson, 2002;Porter & Smithson, 2001;Wilson & Floden, 2001) and a second, more recent line, focuses on teachers' response to assessment and accountability (e. g., Grant, 2001;Kannapel et al, 2000;Mabry, Poole, Redmond, & Schultz, 2003;Stecher et al, 2000;Whitford & Jones, 2000). In certain cases, scholarship in these lines has informed the critiques of the unresolved equity agenda of standards-based reform.…”
Section: Teacher-centric Research On Standards-based Reformmentioning
confidence: 99%
“…The challenge for all states, however, is to assure the translation or transfer of state standards to local school districts and, eventually, to teachers where implementation takes hold (Dutro, Fisk, Koch, Roop &Wixson, 2002;Stecher, Barron, Chun, & Ross, 2000;). While it might be assumed that local participation in state standards development would facilitate some degree of transfer, research clearly indicates that school districts play a crucial role in reform, filtering and shaping information states hope will influence classroom practice (Cohen & Hill, 2000;Hertert, 1996;Marsh, 2000;Spillane & Jennings, 1997;Standerford, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The most effective professional growth activities are teacher-directed, where teachers lead the process to create, present, and collaborate in professional development activities to improve learning outcomes (Akiba & Liang, 2016;Stillman, 2011;Wilson & Berne, 1999). Models of professional development that are content focused and involve a critical mass of teachers in the building were more successful in changing culture, practices, and lead to deeper conversations and reflections on their own as well as their colleagues' teaching (Dutro, Fisk, Koch, Roop, & Wixson, 2002;Gallucci, 2003). In a study of 25 public, private, and religiously affiliated school principals on the U.S. east coast, Drago-Severson (2007) found that principals who demonstrated exemplary behaviors to encourage teacher growth were highly collaborative, and shared authority over professional development with their teachers.…”
Section: Principals' Roles In Professional Development Leadershipmentioning
confidence: 99%